Unsur Budaya dan Karakter Tokoh dalam Novel Gajah Mada Sumpah di Manguntu Karya Langit Kresna Hariadi - Sujoko Sujoko (Universitas PGRI Palembang, 2016)
The problems in this paper were (1) how the cultural elements contained in Novel Gajah Mada Oath in Manguntur works Langit Kresna Hariadi (2) how the characters in the novel Sumpah Gajah Mada in Manguntur work Kresna Hariadi sky. The purpose of this study was describe the cultural elements and characters. The method used descriptive analytic method. Based on the results of this study concluded that the novel Sumpah Gajah Mada in Manguntur contain many elements of culture, especially Javanese culture in the era of the Majapahit Kingdom as reflected through the various series of events in the novel. The element of trust towards various things like believing in the power of dreams and believing in the magical powers that are found in a variety of series of stories. So also in other cultural elements such as information technology becomes an interesting fact that in the era of the Majapahit empir, pigeons and gong used as a means of information. Other cultural elements obtained in this study was the language elements are enough to dominate. Java language shaped imagery and idioms are found in this study. Keywords: culture, characters, Java